Curriculum for a New Five-Year Academic Program in Intelligent Systems Engineering and Software Engineering - Solo, Ashu M. G. (Proceedings (International Conference on Computational Science and Computational Intelligence), 2023)
This research paper proposes a curriculum for a five-year academic program with a bachelor's degree (honors) in intelligent systems engineering and software engineering and a master's degree in intelligent systems engineering and software engineering. This program includes courses in data structures, compiler design, operating system design, firmware design, database systems, computer graphics and virtual reality design, static and dynamic website design, development of chatbots and voice assistants, software engineering methodology, knowledge-based systems, fuzzy logic, neural networks, evolutionary computation, evolutionary multiojective optimization, machine learning, image processing, computer vision, pattern recognition, voice recognition, natural language processing, data science, control systems, intelligent control systems, robotics, digital signal processing, mathematics, engineering physics, biology, etc. These degrees will allow graduates to have a good understanding of all of the main branches of intelligent systems engineering and software engineering as well as other relevant subjects in electrical and computer engineering.